Improved Microcontroller-Based 3 Phase Induction Motor Protection From A Variety Of Interruptions - Efri Wildan Hafiz; Tarigan, Adi Sastra P.; Solly Aryza (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Different types of human labour in the contemporary era of globalization rely on electronic tools like 3-phase induction motors. The usage of a 3-phase induction motor in this investigation is essential for synchronized gait and function. Due to differences in the R, S, and T phase angles, which result in an uneven load overload in the electricity distribution system, voltage changes between the three phases of the electrical energy system arise. Overvoltage, Undervoltage, Unbalanced Inter-Phase Voltage (unbalance voltage), Overload (overload), and Overheat are a few of the issues that might arise. In response to this conflict, a three-phase induction motor protection system was developed.